Paranoia - Freeman, Daniel (Oxford University Press, 2008)
In this entertaining and thought-provoking book, based on the most up-to-date scientific research, Daniel and Jason Freeman highlight just how prominent paranoia is today. One in four of us have regular paranoid thoughts. The authors analyse the causes of paranoia, identifying the social and cultural factors that seem to be skewing the way we think and feel about the world around us. And they explain why paranoia may be on the rise and, crucially, what we can do to tackle it. Witty, clear, and compelling, Paranoia takes us beyond the tabloid headlines to pinpoint the real menace at the heart of twenty-first century culture